Formation of the Protein Corona: The Interface between Nanoparticles and the Immune System. (December 2017) - Barbero, Francesco; Russo, Lorenzo; Vitali, Michele; Piella, Jordi; Salvo, Ignacio; Borrajo, Mireya L.; Busquets-Fité, Marti; Grandori, Rita; Bastús, Neus G.; Casals, Eudald; Puntes, Victor
Abstract: The interaction of inorganic nanoparticles and many biological fluids often withstands the formation of a Protein Corona enveloping the nanoparticle. This Protein Corona provides the biological identity to the nanoparticle that the immune system will detect. The formation of this Protein Corona depends not only on the composition of the nanoparticle, its size, shape, surface state and exposure time, but also on the type of media, nanoparticle to protein ratio and the presence of ions and other molecular species that interfere in the interaction between proteins and nanoparticles. This has important implications on immune safety, biocompatibility and the use of nanoparticles in medicine.